ANALISIS STRES DAN PENGARUHNYA TERHADAP KINERJA PENGUSAHA INDUSTRI KECIL (Studi Kasus pada Centra Industri Konveksi Di Kecamatan Wedi Kabupaten Klaten) - Wibisono Adi, Arif (Universitas Muhammadiyah Surakarta, 2000)
The role of the entrepreneurs in the home industry is very importan, because they are the owners and also the managers, and in the home industry there is still no distribution of tasks of different managerial fields, such as marketing, accountant, human resource, production, and financial fields. All of the tasks are handled by the entrepreneurs themselves.To increase the productivity of the industry, the entrepreneurs must improve their knowledge, their skills, and their psychological condition. One of the crucial psychological condition is the problem of stress. The twentieth century is well-known as âthe Age of Anxiety of Stressâ. Stress gives negative impacts on the well-being of the people.It has been suggested that hight level of the stress gives negative impact on the performance of the entrepreneurs. But it is not only the level of stress, but also the kind of stressors and the way of stress coping give the contribution to the effect of stress on the performance.This research aimed to study the effect of stress on the performance of the garment entrepreneurs at Kecamatan Wedi Kabupaten Klaten by the case study method. To collect the data, it was used questionnaires, interviews and observations. The technique of analysis was quantitative descriptive.This case study involved four young adult entrepreneurs (1 female, 3 males) as samples, out of 141 garment entrepreneurs as the population. It was used purposive sampling technique.It was found that the higher the level of the stress, the more negative the performance but it must be considered the stressors and the stress coping behavior. If the stressors are problems of human relation in the family, the negative effects will be greater than the non human relation stressors. If the stress coping is problem-oriented, the negative effects will be smaller than the emotion-oriented way of the stress coping.